O acontecimento de corpo em um caso de síndrome de pânico - Franca, Georgiana Furtado (2008)
This study aims at analysing the physical symptoms triggered by panic disorder not only its merely physiological reactions but also the way they are psychologically organized, that is to say, the corporal demeanour as viewed by Czermak, When referring to real clinic in Lacan, who privileges the body and its intensities. It is a psychoanalytic research, on which we will use fragments of a clinical case of a 29 year-old young man, married, whose psychiatric diagnosis is Panic Disorder. Our purpose is to search for metapsychological meanings of the revealed physical symptoms. To accomplish this, we will present the meanings expressed by the patient in relation to his corporal symptoms, by means of distinction between such meanings and the physiological manifestations caused by panic, described on the disorder. The corporal representations will be taken as a corporal memory that is revealed oh the transfer. Our aim is to comprehend, with the analysis of the fragments of the studied case, how the corporal demeanour organizes it self psychologically, by means of the interpretation method suggested by psychoanalysis. As theoretical basis for discussion of such issues, we will consider Freud's ideas, according to Basto's view as well as contemporary authors who treat the body in clinic, like Paul Laurent Assoun, Piera Aulagnier, Ivanise Fontes and Maria Helena Fernandes. The analysis of the fragments has indicated that it is possible to identify the organization of the rising subjectiveness throuem body demeanour present in the physical symptoms of panic.